Asian seabass (Lates calcarifer) larval rearing using cyclopoid copepod (Apocyclops royi) live feed: A new approach - Radha Vijayaraj; Mani Jayaprakashvel; Kareem Altaff (Journal of Basic and Applied Zoology)
Abstract Background The Apocyclops species are gaining importance as suitable live feed for augmenting growth and survival of marine finfish larvae. In the present study, as a new approach Apocyclops royi is mass cultured using monoalgal diet (Chloroidium saccharophilum) and its nutritive value is assed and used as supplementary diet in the Asian seabass Lates calcarifer larval rearing. Results Mass culture of A. royi with C. saccharophilum diet reached population density of 12,700 ± 454 ind./L on 21 days culture period. A. royi showed high ratio of DHA:EPA and EPA: ARA. Rearing experiments of the Asian seabass (Lates. calcarifer) 11 DPH larvae with copepod, Artimia nauplii and their combination diets recorded faster growth and maximum survival (90%) with A. royi + Artemia nauplii diet compared to A. royi and Artemia nauplii lone feeds. Seabass larval length and weight gain showed significant (p < 0.05) difference among the three dietary treatments. Significantly high content of essential fatty acids in the L. calcarifer larvae have been reported in A. royi + Artemia nauplii fed seabass larvae compared to individual A. royi and Artemia nauplii fed larvae. Conclusions Our finding highlights the importance of incorporating A. royi as a supplementary feed for seabass larvae, which will bring improvement in their growth and survival leading to sustainable seed production of this fish.